2020
DOI: 10.21608/ejabf.2020.76557
|View full text |Cite
|
Sign up to set email alerts
|

First record of Bryde's whale (Balaenoptera brydei, Olsen, 1913) in the southeastern Mediterranean Sea, Alexandria, Egypt

Abstract: Pectoral fin total Width (Pect. F): The distance from the fin origin to the end of the free rear tip. Pectoral fin upper posterior margin (Pect. H1): The distance between the tip of the fin and the deepest point of the concave curve of the posterior margin. Pectoral fin lower Posterior margin (Pect. H2): The distance between the deepest point of the concave curve of the posterior margin to the posterior end of the dorsal fin. Pectoral fin posterior margin (Pect. I): The distance between the fin tip and the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The most recent of which was in February 2021 in southern Palestine, a few kilometers from the north of the Gaza Strip, where a dead specimen of a Fin Whale measuring 17 meters in length stranded. The multiplicity of strandings of both baleen and toothed whales on the small coast of the Gaza Strip, which is 42 km long, demonstrates the importance of the eastern Mediterranean basin in housing a considerable number of cetaceans as a lot of studies demonstrated (Weitkowitz, 1992;Öztürk and Öztürk, 1998;Kerem et al, 2012;Khalaf et al, 2003;Bazairi et al, 2010;Öztürk et al, 2011;Dede et al, 2012;IUCN, 2012;Shoham-Frider et al, 2014 and2016;Gaspari et al, 2015;Bearzi, 2017;Farrag et al, 2019;Abo-Taleb, 2020 andStephens et al, 2021). As an indication of the importance of the Palestinian Mediterranean waters in harboring a diversity of cetaceans; particularly dolphins, a 2,000-year-old and 16-inch dolphin statue clutching a fish between its jaws, carved During the last 40 years, some old Gazan fishermen who used to fish far from the shore off the coast of Gaza or even the Egyptian coast admitted that they were able to see some baleen whales at sea for very short periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent of which was in February 2021 in southern Palestine, a few kilometers from the north of the Gaza Strip, where a dead specimen of a Fin Whale measuring 17 meters in length stranded. The multiplicity of strandings of both baleen and toothed whales on the small coast of the Gaza Strip, which is 42 km long, demonstrates the importance of the eastern Mediterranean basin in housing a considerable number of cetaceans as a lot of studies demonstrated (Weitkowitz, 1992;Öztürk and Öztürk, 1998;Kerem et al, 2012;Khalaf et al, 2003;Bazairi et al, 2010;Öztürk et al, 2011;Dede et al, 2012;IUCN, 2012;Shoham-Frider et al, 2014 and2016;Gaspari et al, 2015;Bearzi, 2017;Farrag et al, 2019;Abo-Taleb, 2020 andStephens et al, 2021). As an indication of the importance of the Palestinian Mediterranean waters in harboring a diversity of cetaceans; particularly dolphins, a 2,000-year-old and 16-inch dolphin statue clutching a fish between its jaws, carved During the last 40 years, some old Gazan fishermen who used to fish far from the shore off the coast of Gaza or even the Egyptian coast admitted that they were able to see some baleen whales at sea for very short periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, which is a very close country to Palestine, many recent studies relating to cetaceans were reviewed (Notarbartolo et al 2017; Dawoud et al, 2016;Farrag et al, 2019;Abo-Taleb, 2020;and Mahdy et al, 2021). In Turkey, Iran, Lebanon and Syria, many cetaceans were studied for their biology, ecology and stranding (Öztürk and Öztürk, 1998;Khalaf et al, 2003;Saad, 2004;Öztürk et al, 2011 andDede et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 78 known species, 22 have been recorded in the Mediterranean basin. The last species recorded in a recent stranding event is the first record of the Bryde's whale, Balaenoptera edeni (following nomenclature according to Kato and Perrin 2018 [34]), along the Egyptian coast [35].…”
Section: The Study Areamentioning
confidence: 99%
“…Until recently it was thought neither species occurred in the Mediterranean or the Red Sea (National Oceanic and Atmospheric Administration, 2022a, 2022b). However, humpbacks and members of the Bryde's whale complex have been reported in the Red Sea (Notarbartolo di Sciara et al, 2017), while a Bryde's whale was also stranded off the coast of Alexandria in 2018, demonstrating at least an occasional presence in the Mediterranean (Abo‐Taleb et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, humpbacks and members of the Bryde's whale complex have been reported in the Red Sea (Notarbartolo di Sciara et al, 2017), F I G U R E 1 Range of Bryde's whale complex and humpbacks (after the NOAA Fisheries Species Directory 2022a, 2022b) and the locations of trap feeding behaviors by humpbacks off Vancouver Island (a) and tread-water feeding by Bryde's whales in the upper Gulf of Thailand (b). while a Bryde's whale was also stranded off the coast of Alexandria in 2018, demonstrating at least an occasional presence in the Mediterranean (Abo-Taleb et al, 2020). Trap or tread-water feeding is a specialist hunting technique, where a rorqual whale positions itself vertically in the water with only the tip of its snout and mandible (jaw) protruding from the surface, or with its rostrum in a near vertical position and its mandible horizontally near the water's surface (Figure 2).…”
Section: Marine Biological Backgroundmentioning
confidence: 99%